Análise e proposta de melhoria na segurança quando utilizado andaime suspenso em canteiros de obras no Vale do Rio Pardo – RS - Frantz, Josiane Luiza (Universidade do Vale do Rio dos Sinos, 2016)
The construction industry is responsible for a large number of work-related accidents in Brazil. We surveyed several building sites in the Rio Pardo River Valley region to analyze the safety level in the utilization of suspended scaffolds. In order to achieve our goal, based on the interviews we conducted with the engineers responsible for each site and through an in loco analysis, we filled out a standard checklist. At the end of the analysis we identified a significant number of safety issues in the facilities and in the workflow of most of the visited sites, especially in one of them, which had a compliance rate of only 28% of the checked items. Our improvement recommendations include all the building sites since all of them exhibited some degree of safety deficiency in their activities.
Keywords: Canteiros de obras; Segurança; Trabalho; Máquinas; Equipamentos; Building sites; Safety; Work; Machines; Equipment